MOTIVASI MAHASISWA MEMILIH JURUSAN SOSIOLOGI (Studi Terhadap Mahasiswa Sosiologi Angkatan 2022 FISIP UNRI) - Z, Popy Zalita; ', yesi (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research was conducted at the Faculty of Social and Political Sciences, Riau University, Pekanbaru City. The purpose of this research is to find out: 1) what is the motivation of students to choose the Department of Sociology at FISIP UNRI, 2) What are the dominant factors in determining the choice of major for sociology students class of 2022 at FISIP, Riau University?. This research uses a descriptive quantitative method. Data collection techniques in this study were observation, questionnaires, and documentation. This study used simple random sampling, where there were 46 respondents. The data analysis technique in this study was descriptive quantitative using SPSS version 23. The results of the research on student motivation in choosing a sociology major can be seen that because of the need for achievement, every individual wants to excel in any way. There is a need for power, because it has become the greatest human desire to rule, and a need for affiliation, because human beings are social creatures who need to make friends, interact and socialize. The results of the study of the factors determining the selection of majors that affect student motivation in choosing a sociology major can be seen that there are 5 factors that influence it, namely parents, peers, environment, gender (gender), individual personality characteristics.. Keywords: Motivation, Selection of Major, Sosiologi Student